Folate Receptor Beta for Macrophage Imaging in Rheumatoid Arthritis - Steinz, Maarten M.; Ezdoglian, Aiarpi; Khodadust, Fatemeh; Molthoff, Carla F. M.; Srinivasarao, Madduri; Low, Philip S.; Zwezerijnen, Gerben J. C.; Yaqub, Maqsood; Beaino, Wissam; Windhorst, Albert D.; Tas, Sander W.; Jansen, Gerrit; et al. (Frontiers in Immunology, 2022)
Non-invasive imaging modalities constitute an increasingly important tool in diagnostic and therapy response monitoring of patients with autoimmune diseases, including rheumatoid arthritis (RA). In particular, macrophage imaging with positron emission tomography (PET) using novel radiotracers based on differential expression of plasma membrane proteins and functioning of cellular processes may be suited for this. Over the past decade, selective expression of folate receptor β (FRβ), a glycosylphosphatidylinositol-anchored plasma membrane protein, on myeloid cells has emerged as an attractive target for macrophage imaging by exploiting the high binding affinity of folate-based PET tracers. This work discusses molecular, biochemical and functional properties of FRβ, describes the preclinical development of a folate-PET tracer and the evaluation of this tracer in a translational model of arthritis for diagnostics and therapy-response monitoring, and finally the first clinical application of the folate-PET tracer in RA patients with active disease. Consequently, folate-based PET tracers hold great promise for macrophage imaging in a variety of (chronic) inflammatory (autoimmune) diseases beyond RA.